THE INFLUENCE OF LEADERSHIP STYLE, WORK ENVIRONMENT AND COMPENSATION ON EMPLOYEE LOYALTY AT UD. KARYA SARANA JAKARTA TIMUR - Reski Daffa Adrian Dunda; Bambang Purwoko Kusumo Bintoro (Jurnal Scientia, 2023)
The purpose of this study was to analyze the relationship between the influence of leadership style, work environment and compensation on employee loyalty at UD. Karya Sarana East Jakarta. In this study, the sample was employees at UD. Karya Sarana East Jakarta with a total sample of 60 people. This study uses quantitative methods with probability sampling technique (random sample), and data analysis tools using SPSS version 25.0 program. Based on the results of research at UD. Karya Sarana, East Jakarta, shows that Leadership Style has a significant positive effect on Employee Loyalty, Work Environment also has a significant positive effect on Employee Loyalty and Compensation has a significant positive effect on Employee Loyalty, such as Leadership Style, Work Environment and Compensation Together (simultaneously) has a positive and significant effect on employee performance.